Interventions for preventing silent cerebral infarcts in people with sickle cell disease (Protocol) - Estcourt, L; Fortin, P; Hopewell, S; Trivella, M; Doree, C; Abboud, M (John Wiley & Sons, Ltd, 2016)
This is the protocol for a review and there is no abstract. The objectives are as follows: To assess the effectiveness of red blood transfusions and hydroxyurea alone or in combination and HSCT to reduce or prevent SCI in people with SCD.